Das Ende der Tage und die Gegenwart des Heils : Begegnungen mit dem Neuen Testament und seiner Umwelt : Festschrift für Heinz-Wolfgang Kuhn zum 65. Geburtstag - Kuhn, Heinz-Wolfgang.; Becker, Michael, 1958 January 17-; Fenske, Wolfgang. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1999)
This volume combines articles of established scholars on Jewish and New Testament studies in honor of the New Testament scholar Prof.Dr. Heinz-Wolfgang Kuhn, Munich. The articles deal with various aspects of his work on the Dead Sea Scrolls, Archeology (Bethsaida), Jewish and New Testament Studies. Some of the contributions focus especially on aspects of eschatology in the time of the first century.